Development of an application tool to support returnees in Fukushima. Issue 1 (July 2021) - Ohba, T.; Goto, A.; Nakano, H.; Nollet, K.E.; Murakami, M.; Koyama, Y.; Honda, K.; Yoshida, K.; Yumiya, Y.; Kuroda, Y.; Kumagai, A.; Ohira, T.; et al.
To promote radiation protection and health promotion among returning residents (returnees) in coastal areas of Fukushima, eHealth principles were used to develop a new application tool (app) that can record radiation exposure and health status while providing comprehensive support to returnees. Intended users are returnees and health and welfare workers. After assessing their needs, a flowchart and prototype for operational logic were created using commercially available software tools. Professional developers will focus on improving the user interface and ensuring data security. The finished app will be compatible with mobile telephones and tablets. Utility and ease of use are paramount to serve returnees of all ages effectively.